Optimalisasi Penggunaan Media Sosial dalam Tujuan Peningkatan Engagement serta Digitalisasi Komunitas Desa Sungai Rengas Kecamatan Sungai Kakap Kabupaten Kubu Raya - Adelin, Videlia; Hudjah, Anisa Madinahtul; Ahira, Andi Putri (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Villages are ideal communal milestones for social community standards. Explore the potential of social media to increase community engagement and encourage the digitalization of rural areas. As global connectivity continues to increase, social media has become an indispensable tool for communication and development even in the most remote areas. This research investigates how social media can empower the people of Sungai Rengas Village, Sungai Kakap District, Kubu Raya Regency to increase social cohesion, economic growth, and access to important services. This research also discusses digital literacy and infrastructure challenges facing rural areas and suggests strategies to overcome these barriers to fully realize the benefits of social media. The foundation of this research draws on key theories of digital transformation and community engagement to provide a framework for future community service initiatives.